Staff Roles in Quality Assurance in Education at Phranakhon Rajabhat University - อ้อยแดง, งามพิศ (Academic and Research Journal of Liberal Arts (Online), 2018)
This research aimed to study 1) the staff roles, the factors involved the staff roles and the guidelines to develop the staff roles in quality assurance in education at Phranakhon Rajabhat University. The population was 257 staff with both the academic and the support staff members from 5 faculties. The research applied mixed methods design. The qualitative data were collected with an in-depth interview from 12 staff members and analyzed with content analysis and triangulation method. The questionnaire with the coefficient correlation of 0.77 was used as an instrument to collect quantitative data. The descriptive statistics to analyze the quantitative data included frequency, percentage, mean and standard deviation. The results showed that: 1) The staff roles in quality assurance in education consisted of four aspects : (1) In planning step was found at a high level; (2) In doing step was found at a high level; (3) In checking step, the checking of related documents and evidences in accordance with the standard quality was found at a high level; and (4) In acting step was found at a high level. 2) There were 4 factors that involved the staff roles in quality assurance in education: knowledge, cooperation, motivation, and support: (1) In terms of knowledge, the staff possessed practical knowledge of filing and keeping all crucial documents in accordance with the standard quality was found at a high level; (2) In terms of cooperation at a moderate level; (3) In terms of motivation, the staff believed that the drive to produce quality work would guarantee the quality assurance was found at a high level; and (4) In terms of support at a moderate level. 3) The proposed guidelines to develop the staff roles in quality assurance in education at Phranakhon Rajabhat University included 4 measures: (1) to develop awareness about quality assurance; (2) to encourage cooperation in preparing for quality assurance; (3) to enhance positive attitude to quality assurance; and 4) to increase motivation for maintaining quality assurance.